PENINGKATAN HASIL BELAJAR PENYAJIAN DATA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN GAMMA DI KELAS IV SDN 02 JAMBAK KABUPATEN PASAMAN - Farhani, Rahadatul; Zainil, Melva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of fourth-grade students at SDN 02 Jambak, Pasaman Regency. Classroom learning was still teacher-centered, the use of learning media was less engaging, and teachers were not yet optimal in implementing problem-based mathematics learning. These conditions affected students’ ability to absorb information effectively. Therefore, this study aimed to describe the improvement of students’ learning outcomes in data presentation through the implementation of the Problem Based Learning (PBL) model assisted by Gamma in class IV of SDN 02 Jambak, Pasaman Regency. This study was a Classroom Action Research (CAR) employing both qualitative and quantitative approaches. The research was conducted in two cycles, namely Cycle I and Cycle II. Cycle I consisted of two meetings, while Cycle II was conducted in one meeting. Each cycle included four stages: planning, implementation, observation, and reflection. The subjects of this study were 18 fourth-grade students of SDN 02 Jambak, Pasaman Regency, consisting of 6 boys and 12 girls. The results of the study showed an improvement from Cycle I to Cycle II. The observation score of the teaching module in Cycle I reached an average of 81.25% in the good category (B), and increased to 96.8% in the very good category (SB) in Cycle II. In terms of teacher activities, the observation results in Cycle I showed an average of 83.9% in the good category (B), which improved to 92.86% in the very good category (SB) in Cycle II. Meanwhile, in the student activity aspect, the average score in Cycle I was 73.21% in the fair category (C), increasing to 89.28% in the good category (B) in Cycle II. The students’ learning outcomes in Cycle I obtained an average score of 74.7 in the fair category (C), which then increased to 91.1 in the very good category (SB) in Cycle II. Thus, it can be concluded that the implementation of the Gamma-assisted Problem Based Learning model was able to improve students’ learning outcomes in data presentation learning in class IV of SDN 02 Jambak, Pasaman Regency.